Thinking Outside the Box at Open-Air Archeological Contexts: Examples From Loess Landscapes in Southeast Romania - Fitzsimmons, Kathryn E.; Doboş, Adrian; Probst, Mathias; Iovita, Radu (Frontiers in Earth Science, 2020)
Stratified, well preserved sites preserving unambiguous geological and archeological data from which human-environmental interactions can be reconstructed, are rare. More commonly we must test our hypotheses based on extrapolation of the few available sites, particularly in regions with high sedimentation rates. Here we test the idea of aggregating “off-sites”—human traces which provide isolated evidence of activity in an area—to maximize the information which can meaningfully be extracted from Paleolithic open-air contexts. We present two case studies from the sediment-rich loess steppe of southeast Romania, Lipniţa and Dealul Peşterica. Both off-sites preserve low density, undiagnostic lithic assemblages which may otherwise be overlooked in favor of more impressive sites. We constrain the timing of occupation at these two localities to c. 61 and 34–41 ka at Lipniţa and Dealul Peşterica, and show that people were present near a river bank and on loess slopes respectively. Aggregation of data from the region suggests repeated visitation of riverine landscapes; additionally people likely ranged across landforms, particularly where raw material for making stone tools was plentiful. Our case studies demonstrate that empirical, incremental findings may still be generated from sites traditionally thought to be of little value. We argue that this approach is highly applicable to investigating the human implications for landscape context from archeological traces in sediment-rich, open-air situations.